Kalender Hijriyah Dalam A-Qur'an - Musa Al-Azhar (University of Muhammadiyah Sumatera Utara, 2018)
In this article, an in-depth study of the secrets of creation of the Moon in the Qur'an is presented in relation to the calendar (taqwîm). As you know, the Moon has a regular path by which humans can know the number of the moon, because it rotates, starts from one point and returns to the same point. So, it can be taken a conclusion that with the condition of the Moon evolving towards the Earth with a regular trajectory, humans can calculate it so that it can be used for calendar purposes.Keywords: Al-Qur'an, calendar, month